Implementasi Metode Relasional Pada Konselling Pribadi Sosial Terhadap Siswa/i di Sekolah - Selsa Ivana; Nafa Artha Fadiyah; Qurratu Aini; Gusman Lesmana (PT. ALHAFI BERKAH INDONESIA, 2023)
The purpose of this research is to explore the personal character of students, to be aware of the wrong and deviant behavior that students have done at school through personal social counseling activities with a relational approach. The research method used is literature review sourced from journals/articles, books related to social personal counseling of students at school. The results of the study concluded that the application of personal social counseling with a relational approach model made students more comfortable and calm when the counselor explored their experiences. Likewise, in this approach model a counselor must be able to communicate with a student in terms of respecting a student's personal self, understand the student's personal world through empathy, be aware of and share experiences with students at school about what they have experienced. natural counselor openly, away from the attitude of something that is not true (artificial).